AUTOCHTHONOUS PLANT GENETIC RESOURCES AND THEIR USES FOR SUSTAINABLE DEVELOPMENT - Vilela-Morales, Eduardo Alberto; Candeira Valois, Afonso Celso (Science & Technology Journals, 2000)
The present article looks for an increased use of autochthonous plant genetic resources in order to reduce the dependence of Brazil on exotic species. It makes reference to the abundance of genetic resources in the Country and their importance for development of sustainable agriculture, and opens a discussion about the alternative ways for using its own biodiversity.